2017
DOI: 10.1016/s2213-2600(17)30234-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of early administration of simvastatin in the prevention and treatment of delirium in critically ill patients undergoing mechanical ventilation (MoDUS): a randomised, double-blind, placebo-controlled trial

Abstract: National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 39 publications
5
70
0
3
Order By: Relevance
“…In that study of 229 patients undergoing cardiac surgery, 126 (55.0%) had developed POCD by 1-year follow-up and statin use at discharge was unrelated to POCD risk (RR 1.10; 95% CI 0.87 to 1.38; P=0.441) 42. Two trials were excluded from our analysis due to non-English language43 or initiation of statin treatment after surgery 44. One Russian study compared the effects of preoperative rosuvastatin treatment for 10 to 14 days before surgery and until hospital discharge versus not receiving that treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study of 229 patients undergoing cardiac surgery, 126 (55.0%) had developed POCD by 1-year follow-up and statin use at discharge was unrelated to POCD risk (RR 1.10; 95% CI 0.87 to 1.38; P=0.441) 42. Two trials were excluded from our analysis due to non-English language43 or initiation of statin treatment after surgery 44. One Russian study compared the effects of preoperative rosuvastatin treatment for 10 to 14 days before surgery and until hospital discharge versus not receiving that treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Here, either simvastatin or placebo was administered to 142 patients and no effect of intervention on risk of POCD 6 months after surgery was found 44. However, that study was of critically ill patients, and so is not necessarily representative of the general older population undergoing surgery, had high loss to cognitive follow-up (66.2%) and, unlike the Russian trial,43 initiated statin treatment immediately after surgery 44. Effects of longer-term preoperative statin use on POCD risk were not addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six RCTs were identified: haloperidol (n = 2) (380, 381), atypical antipsychotics (quetiapine) (n = 1) (382), ziprasidone (n = 1) (380), olanzapine (n = 1) (383), and a statin (i.e., rosuvastatin) (n = 1) (384). A recent randomized trial of critically ill adults, not included in the evidence profile, found that high-dose simvastatin does not reduce days spent with delirium and coma (385). No evidence was found to inform a recommendation regarding the use of an NMDA antagonist (e.g., ketamine) for delirium treatment.…”
Section: Delirium Treatmentmentioning
confidence: 99%
“…Several retrospective and prospective cohort studies have found that statin use in ICU patients is associated with a reduced risk of delirium 70,71 ; however, 2 recent randomized control trials showed no benefit to statins in preventing ICU delirium. 72,73 Treatment Initial management of delirium should involve treating any identifiable precipitating factors. Further management goals are aimed at reducing its severity and duration.…”
Section: Preventionmentioning
confidence: 99%